THE SYNTHESIS OF GLYCEROL CARBONATE FROM BIODIESEL BYPRODUCT GLYCEROL AND UREA OVER AMBERLYST 36 (Jurnal Bahan Alam Terbarukan, 2017)
The increasing use of biodiesel as renewable fuels leads to the increasing of glycerol amount as a byproduct of biodiesel production. One of the glycerol derivative products that is environmentally friendly and renewable is glycerol carbonate. Glycerol carbonate is commonly used as a raw material for polymers, surfactants, emulsifiers, lubricants, paints, also used in the cosmetics and pharmaceutical industries. In this study, the research was carried out by using a batch reactor with a three-neck flask equipped with reverse cooling, thermometers, mercury stirrer, and heating mantle with the conditions of the reaction temperature around 373 – 413 K, mole ratio of reactants of urea: glycerol were 1:0,5, 1:1, 1:1,5, 1:2 and 1:4  and the concentration of catalyst were 1%, 2%, 3%, 4% and 5% respectively. Reaction was done for four hours. The results showed that the formation of glycerol carbonate from glycerol and urea using a catalyst Amberlyst 36 is affected by the catalyst concentration, reaction temperature and the ratio of reactants used. The highest glycerol conversion was obtained at 55.07% at a temperature of 393 K with mole ratio of urea and glycerol 1:0,5 and the percentage of catalyst 3% of the amount of glycerol.